Financial development and income inequality: a nonlinear econometric analysis of 21 African countries, 1990-2019 - Lindokuhle Talent Zungu; Lorraine Greyling; Irrshad Kaseeram (Cogent Economics & Finance, 2022)
From 1990 to 2019, this study examines the nonlinear dynamic impact of financial development on income inequality in an unconventional policy regime in a panel of 21 African countries. More importantly, we use Panel Smooth Transition Regression to extend the existing debate on this subject, with roots back to the seminal work of G-J and many others, and add a twist by distinguishing between a conventional (1990-1999) and unconventional policy regime (2000-2019), as well as the threshold level at which financial development reduces inequality. Our baseline results will be supported by the Generalized Method of Moments. The PSTR model was chosen because it can account for features that dynamic panel techniques cannot, such as endogeneity, homogeneity, cross-country variability, and time instability within the model. We found evidence of a non-linear effect between the two variables, with the threshold found to be 21.90% of GDP, below which financial development reduces inequality in Africa, and this confirms the U-shape in unconventional policy regimes and the G-J in conventional policy regimes. Unconventional monetary policies were found to trigger the financial-inequality relationships. The focal policy recommendation is that the financial sector be given adequate consideration and recognition by, inter alia, implementing appropriate financial reforms, developing an adequate investment strategy, and maintaining spending on science and technology investment in African countries below the threshold. Again, when implementing unconventional monetary policies in African countries, extreme caution is required.
Keywords: 330; conventional monetary policy; financial development; income inequality; PSTR model; unconventional monetary policy